INVESTIGATION ON IN VIVO ANALGESIC ACTIVITY OF METHANOL EXTRACT OF MARINE BROWN ALGA SPATOGLOSSUM ASPERUM J. AGARTH - M, Pandithurai; S, Murugesan; V, Sivamurugan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, evaluation of the methanol extract of Spatoglossum asperum, brown marine algae on the analgesic activity using animal model was focussed. Methods: Acetic acid-induced writhing test on Wistar albino rats at a dosage of 10 mg/kg body weight of algal extract have been carried out. It showed significant analgesic activity by reducing the number of acetic acid-induced writhing. Results: The animals at a dosage of 10 mg/kg body weight exhibited, 70.52% of the animals were protected using S. asperum extract, on the other hand, the standard, diclofenac protected 84.21% of the animals. The results are statistically significant at p<0.001, and the investigation revealed dose-dependent significant activity in comparison with standard and control. Conclusion: Hence, it can be concluded that the methanol extracts of the brown alga S. asperum have potent analgesic activity at moderate doses.